Impact of motor vehicles-bicycles interaction on route selection, traffic performance, emissions and safety - Bahmankhah, Behnam (2019)
Mobility in urban areas is highly complex because of the variety of possible facilities and routes, the multitude of origins and destinations, the increase of population and traffic. Increased use of active modes, such as cycling, presents economic and environmental benefits, and contributes to health improvement. However, it can lead to safety concerns such as bicycles sudden or unexpected movements mainly when circulating together with motor vehicles (MVs) or when there is an overtaking situation between MVs and bicycles. The main goal of this doctoral thesis is to quantify and assess the impact of the interaction motor vehicle-bicycle on traffic performance, road safety and emissions to define a multi-objective analysis model of the impacts regarding the use of motor vehicle and/or bicycle. The thesis was focused on three main topics developed based on the evaluation of traffic performance, safety and emissions at urban areas : (i) to perform a multi-objective analysis in an integrated manner of the traffic performance, pollutant emissions and road conflicts between bicycles and MVs at a signalized intersection; (ii) to assess the driving volatility in MV-bicycle interactions at two-lane roundabouts and its impacts on safety, pollutant emissions and traffic performance; and (iii) to analyze the impacts of the overtaking lateral distance between a bicycle and a MV on road safety and energy consumption at two-lane urban roads. Second-by-second bicycle and vehicle dynamic data were collected using GPS travel recorders. The methodology developed in this thesis was applied based on real world case studies at different urban road types in the city of Aveiro, Portugal. The present work uses a microscopic simulation platform of traffic (VISSIM), road safety (Surrogate Safety Assessment Methodology – SSAM) and emissions (Vehicle Specific Power – VSP) to analyze traffic operations, road safety concerns and to estimate carbon dioxide (CO2), nitrogen oxide (NOX), carbon monoxide (CO), and hydrocarbons (HC) pollutant emissions. Furthermore, the Fast Non-Dominated Sorting Genetic Algorithm (NSGA-II) was used in order to address the multi-objective analysis of traffic performance, road conflicts between MVs and bicycles, and emissions. Bicycle Specific Power (BSP) and VSP concepts were used in order to analyze the impacts on cyclist and vehicle energy consumption as well. The findings showed that roundabouts present, in general, better traffic performance (number of stops and travel time reduced in 78% and 14%, respectively) and less emissions (CO2, NOX, and HC decreased 9%, 7%, and 12%, respectively) than other intersections, even with high demand of cyclists (270 bicycles per hour). Regarding safety, roundabout layout lead to more severe conflicts and potential crashes while the number of total conflicts can be reduced significantly (-49%). It was also found that the impact of MVs and bicycles speeds, as well as roundabout design, were more important factors than bicycle volumes at roundabouts. Considering the MV-bicycle interaction at two-lane roundabout, the results of emissions dictated good relationships (R2 > 70%) between acceleration and VSP modes distributions. Finally, the findings showed 50% of overtaking lateral distance (between bicycle and MV) lower than 0.5m in both morning and afternoon peak hours. Moreover, it was found that there was a good fit between overtaking lateral distance and traffic volumes in morning (R2 = 72%) and afternoon (R2 = 67%) peak hours. The findings of this research can be useful for policy makers of the mobility and road safety fields, municipalities, road designers, and traffic engineers.